2017
DOI: 10.1002/aenm.201702655
|View full text |Cite
|
Sign up to set email alerts
|

High Efficiency (>17%) Si‐Organic Hybrid Solar Cells by Simultaneous Structural, Electrical, and Interfacial Engineering via Low‐Temperature Processes

Abstract: Highly efficient organic–inorganic hybrid solar cells of Si‐poly(3,4‐ethylenedioxythiophene):polystyrene sulfonate (PEDOT:PSS) have been demonstrated by simultaneous structural, electrical, and interfacial engineering with low processing temperature. Si substrate has been sculpted into hierarchical structure to reduce light reflection loss and increase interfacial junction area at the same time. Regarding the electrical optimization, highly conductive organic PEDOT:PSS layer has been formulated with low sheet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
67
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(70 citation statements)
references
References 49 publications
(127 reference statements)
1
67
0
2
Order By: Relevance
“…PEDOT:PSS film plays dual roles: 1) as top transparent electrode; 2) as hole-selective contact for n-type crystalline silicon to form a p + -n heterojunction (Figure 19d). The hybrid cells have currently achieved PCEs of over 17%, [308] getting close to a predicated value of over 21%. Optimizing PEDOT:PSS to improve its conductivity and reduce surface carrier recombination at the Si/PEDOT:PSS heterointerface is an efficient way to improve device performance.…”
Section: (27 Of 46)mentioning
confidence: 78%
“…PEDOT:PSS film plays dual roles: 1) as top transparent electrode; 2) as hole-selective contact for n-type crystalline silicon to form a p + -n heterojunction (Figure 19d). The hybrid cells have currently achieved PCEs of over 17%, [308] getting close to a predicated value of over 21%. Optimizing PEDOT:PSS to improve its conductivity and reduce surface carrier recombination at the Si/PEDOT:PSS heterointerface is an efficient way to improve device performance.…”
Section: (27 Of 46)mentioning
confidence: 78%
“…Compared to the normal devices, the inverted ones demonstrate substantially higher fill‐factor FF of 50% under illumination – Table . This can be attributed to a better physical contact between CuI and the fullerene due to suppression of charge carrier recombination when an inorganic layer is deposited on the organic one. Besides, the structure of the CuI layer deposited over C 60 is somewhat different from that being the case when the CuI layer is beneath C 60 (Figure S2, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Hybrid photovoltaic cells are expected to combine the advanced concepts, realized in the still unstable organic‐based devices, with the reliable technologies and reproducibility of effects of the inherently stable inorganic semiconductors . Not surprisingly, the most demonstrative examples are associated with the concept of a bulk heterojunction, in which organic semiconductors, the donor, and acceptor materials, are blended using the solution techniques.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] In light-emitting devices, free charges trapped in the defect states cause nonradiative recombination and hinder the charge transport, thereby lowering the photoluminescence quantum yield. [9][10][11] yielded PCEs up to ≈17% [40][41][42][43][44] In addition, additional doping processes or high-temperature vacuum processes involving the deposition of a-Si:H on the rear-side of Si are usually adopted to enhance the cell performance. [41,43,[45][46][47] D. Zielke et al [47][48][49] suggested "BackPEDOT" concept, in which PEDOT:PSS is spin-coated on the backside of the Si substrate.…”
Section: Introductionmentioning
confidence: 99%